Comparative genomic analysis reveals starvation survival systems in Methanothermobacter thermautotrophicus ΔH. (August 2020) - Prathiviraj, R.; Chellapandi, P.
Abstract: Methanothermobacter thermautotrophicus ΔH (MTH) is a thermophilic hydrogenotrophic methanogenic archaeon capable of reducing CO2 with H2 to produce methane gas. It is the potential candidate in the biomethanation of CO2 and CO in anaerobic reactors and biogas upgrading process. However, systematic studies addressing its genome conservation and function remain scant in this genome. In this study, we have evaluated its evolutionary resemblance and metabolic discrepancy, particularly in starvation survival systems by comparing the genomic contexts with Methanothermobacter marburgensis str. Marburg (MMG) and Methanobacterium formicicum DSM 1535 (MFO). The phylogenomic analysis of this study indicated that there was a strong phylogenomic signal among MTH, MMG, and MFO in the whole-genome tree. DNA replication machinery was conserved in the MTH genome and might have evolved at different evolution rates. Genome synteny analysis observed collinearity of either gene orders or gene families has to be maintained with syntenic blocks located in the syntenic out-paralogs. A genome-wide metabolic analysis identified some unique putative metabolic subsystems in MTH, which are proposed to determine its growth characteristics in diverse environments. MTH genome comprised of 93 unique genes-coding for starvation survival and stress-response proteins. These proteins confer its adaptation to nutritional deprivation and other abiotic stresses. MTH has a typical system to withstand its growth and cell viability during stable operation and recovery after prolonged starvation. Thus, the present work will provide an insight to improve the genome refinement and metabolic reconstruction in parallel to other closely related species. Highlights: Comparative genomic analysis revealed starvation survival systems in Methanothermobacter thermautotrophicus ΔH. We inferred core genomic functions and metabolic subsystems are converged across the thermophilic methanogenic archaea. The functional evolutionary process is essential for its adaptation to nutritional deprivation and other abiotic stresses.